Islam's Integration with Local Culture through the Custom of Reciting the Qur'an at Death - Wahid, Annisa; Rahim, Rahimin Affandi Abdul (UIN Sunan Gunung Djati Bandung, 2024)
Lasi, which is in Agam Regency, West Sumatra Province, is an area rich in Islamic culture and traditions. One of the Islamic traditions there is the recitation of death. The tradition of reciting the Qur’an for death is a practice that combines elements of the Islamic religion with local cultural values. This research aims to determine the integration of Islam and local culture manifested in the practice of reciting the Qur’an for death in the Lasi community. The research method used in this research is a field research method that uses a qualitative approach by conducting in-depth interviews with members of the Lasi community who are involved in the tradition of reciting the Qur’an for death. Direct observations were also carried out to understand the implementation of this practice. Qualitative data was carefully analyzed to identify patterns of integration between Islamic religion and local culture in the context of the Qur’an for death. The results of this research reveal that the tradition of reciting the Qur’an for death in Lasi, Agam Regency, reflects close integration between the Islamic religion and local culture. The use of local languages in this tradition strengthens the community's cultural identity, while Islamic religious messages are also maintained. This tradition also plays a role in maintaining Lasi cultural values, connecting the younger generation to their cultural heritage, and strengthening community ties. This integration has helped maintain harmony between religion and culture, creating a model that can serve as an example for efforts to preserve culture and religion in an increasingly globalized society.